Multivisceral Resection with Performing a Double Roux-en-Y Reconstruction for Advanced Gastric Cancer - Zijah Rifatbegovic; Zlatan Mehmedovic; Majda Mehmedovic; Jasmin Hasanovic; Amra Mestric (Case Reports in Surgery)
Background. The role of multivisceral resection, in the setting of locally advanced gastric cancer, is still debated. Previous studies have reported a higher risk for perioperative morbidity and mortality, with limited objective benefit in terms of survival. Patient. A male patient, 55 years old, was admitted to the clinic of surgery for surgical treatment of bleeding gastric ulceration. Preoperative diagnostic evaluation was performed, and patient had undergone a surgical treatment which revealed a large mass in head of the pancreas, infiltrating the hepatoduodenal ligament and transverse mesocolon. Total gastrectomy, duodenopancreatectomy, and right hemicolectomy were performed. The digestive tube continuity was reestablished by deriving the double Roux limbs. Conclusion. The aim of this case presentation is to demonstrate a method of digestive tube reconstruction by performing the double Roux-en-Y reconstruction in advanced gastric cancer when the multivisceral resection is performed.